Pengaruh Green Accounting, Total Asset Turnover, Debt Equity Ratio, dan Kepemilikan Institusional Terhadap Profitabilitas Perusahaan - Thoriq, Iqbal Ghifary; Murni, Yetty; Munira, Mira (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
The purpose of this research is to determine the effect of Green Accounting, Total Asset Turnover, Debt Equity Ratio, and Institutional Ownership on the profitability of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. This research used Green Accounting, Total Asset Turnover, Debt Equity Ratio, and Institutional Ownership as the variables. The data used is secondary data published. The sampling technique used is purposive sampling where based on predetermined criteria, a sample of 10 companies is obtained from a total population of 77 companies. The data analysis method used is panel data regression with the help of the Eviews 9 program. The results show that, Green Accounting and Institutional Ownership have no effect on Profitability. Total Asset Turnover has a positive effect on profitability. Debt Equity Ratio has a negative effect on profitability. Taken together, Green Accounting, Total Asset Turnover, Debt Equity Ratio, and Institutional Ownership affect the profitability of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021.